Neuropsychological Impairment and Rolandic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Universities of Chiete and Salerno, Italy, evaluated the neuropsychological profile of children with rolandic epilepsy (RE) at onset and of their healthy siblings.